Expert System for Diagnosing Mental Disorders at Soeprapto Psychiatric Hospital in Bengkulu Province Using Forward Chaining Method - Ahmad Syukron Ali; Siswanto Siswanto; Jhoanne Fredricka (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
Expert systems are a branch of artificial intelligence designed to mimic the ability of an expert to make decisions or solve problems in a particular field. This study aims to develop a web-based expert system capable of performing diagnoses using the forward chaining method as an inference mechanism. This system is intended to help the public recognize specific problems, particularly in the field of health. Unfortunately, people often lack access to professional psychological services. This study aims to build web-based expert system that can help make an initial diagnosis of mental disorders using forward chaining method. This system is designed to collect symptoms from users, process them using a rule base determined by experts, and provide automatic diagnosis results. In its development, the system uses the PHP programming language and MySQL database to store symptom data, disease information, and consultation results. The inference process is conducted sequentially (forward chaining) based on the symptoms selected by the user until a conclusion is reached regarding the type of mental disorder and its likelihood. Testing results indicate that the system can provide reasonably accurate results in identifying users' mental conditions based on the symptoms entered. This system is expected to serve as a useful initial consultation tool, particularly in communities with limited access to mental health services. However, this system is not intended to replace the role of professionals but rather as a form of technological support to aid in early detection.